Analisis Perencanaan Struktur Perkerasan Apron Pada Bandar Udara Internasional Sultan Hasanuddin Menggunakan Metode FAA - Nasrah, Nasrah; Nurdin, Abdul Rahim; Mallawangeng, Tamrin (Program Studi Teknik Sipil Universitas Bosowa, 2023)
This study aims to determine and analyze thickness of apron pavement structure with Boeing 747-400 aircraft type at Sultan Hasanuddin International Airport using the Federal Aviation Adminstration method. This research is located at Sultan Hasanuddin International Airport Makassar. Data required includes secondary data in the form of aircraft movement traffic data from 2014 to 2018, apron layout and subgrade test California Bearing Ratio data as well as other data. The results of the planning analysis obtained the thickness of apron pavement structure with Boeing 747-400 aircraft type at Sultan Hasanuddin International Airport using the Federal Aviation Adminstration method, the thickness of subbase was 20 cm, base course (stabilized) was 15 cm and surface f’c 33,2 MPa was 41 cm